Excellent Electrochemical Performance of Potassium Ion Capacitor Achieved by a High Nitrogen Doped Activated Carbon. Issue 5 (24th January 2020) - Chen, Zhi; Li, Wenlei; Yang, Jian; Liao, Jiaxuan; Chen, Cheng; Song, Yaochen; Ali Shah, Syed Abbas; Xu, Ziqiang; Wu, Mengqiang
Abstract : Supercapacitors, due to their unique high-power characteristics, are bound to occupy a place in the field of energy storage. Carbon-based supercapacitor is one of the most promising in all material systems. In this work, N-doped/graphene composite activated carbon (AC) is prepared through a facile method as electrodes for the comparison between an aqueous system and an organic system. The obtained AC shows high surface areas of 1600 m 2 g −1 with a high N content of 11.7 wt% and is simultaneously applied to lithium-ions capacitor (LIC), sodium-ions capacitor (NIC) and potassium ion capacitor (KIC). Electrochemical evaluations indicated that the high N-doped activated carbon-based LIC, NIC and KIC possess different performance and energy storage mechanisms. The KIC exhibits the highest energy density of 50 Wh kg −1 at 0.4 A g −1 and the most stable cycle performance of three capacitors. This work reveals differences among the three types of ion capacitors, providing clues for the development of high power-energy and long life ion supercapacitors. Moreover, KIC has better performance than LIC, and the reserve of K is much higher than Li, which makes KIC a better application prospect.